Microbiota associada aos cnidários Millepora alcicornis e Phyllogorgia dilatata: diversidade microbiana e prospecção de moléculas ativas - Macedo, Maria Wanna Figueiredo Sena (2020)
Coral reefs are marine ecosystems that are home to a great biodiversity, forming complex food webs and serving as shelter for various organisms. Due to their high degree of diversity, these environments have a biotechnological potential that is still unknown and little explored, having been studied the produce bioactive molecules organisms, such as polyketides (PKs) and non-ribosomal peptides (NRPs) that can be used in the pharmaceutical, nautical or food industries. Brazilian coral reefs have a unique composition, as they are formed by a large number of endemic species and have a little-found structure, that are named chapeirões. These reefs extend throughout the northeast coast and commonly can be observed the species of stony corals, black corals, fire corals and octocorals. Corals and other marine invertebrate animals have been studied as to their potential in the production of compounds with biological activity, showing a positive result in the studies already carried out, including, evidencing the role of the microorganisms associated with them in the production of these compounds. Due to the increase in global warming and the damage caused to marine environments through anthropic activities, it´s clear the rapid decline in the population number of coral-forming cnidarians reefs. Recently, 90% of the mortality of the species Millepora alcicornis has been observed in the Costa do Descobrimento (BA), as it promotes the search for new ideas for the preservation of reef environments and the study of these ecosystems in relation to their chemical potential. In this study, the corals M. alcicornis and Phyllogorgia dilatata had the cultivable bacterial community associated with them, isolated and identified, using molecular techniques, where it was possible to observe a large number of organisms from the phyla Proeobacteria and Firmicutes, with the majority of the isolates identified as belonging to the Vibrio genus. The bacterial isolates were tested, when the presence of antimicrobial activity, against ATCC strains of Escherichia coli and Staphylococcus aureus, and a positive result was verified for 29 isolates, all belonging to the Vibrio genus. It was also carried out the prospecting of genes encoding enzymes responsible for the synthesis of PKs and NRPs in bacterial isolates, with 27 isolates found that have one of the coding genes. This search also analyzed the relationship between the presence and absence of the gene with a positive result in terms of antimicrobial activity, noting that most isolates that showed amplification of the target gene did not demonstrate antimicrobial activity, a fact that may be related to the presence of silent genes in these samples.